Fertilizer Performance of a Digestate from Swine Wastewater as Synthetic Nitrogen Substitute in Maize Cultivation: Physiological Growth and Yield Responses - Buligon, Eduardo L.; Costa, Luiz A. M.; de Lucas, Jorge [UNESP]; Santos, Francielly T.; Goufo, Piebiep; Costa, Monica S. S. M. (MDPI, 2023)
Nitrogen (N) is the primary nutrient required for plant growth. During the last few decades, there has been extensive use of synthetic N-containing fertilizers in agriculture, resulting in increased environmental pollution. In this study, the feasibility of replacing synthetic N with biofertilizer in maize cultivation was investigated. A liquid biofertilizer (digestate obtained from the anaerobic digestion of swine wastewater) was obtained and applied to large plots as a total (100%) or partial (50%) substitute for synthetic N fertilizer. Moreover, the most efficient fertilization mode, i.e., basal versus foliar application, was studied. Physiological growth indices, leaf nutritional status, and grain yield were assessed for each biofertilization treatment and compared with the conventional treatment with synthetic minerals. Compared with the conventional treatment, the total substitution of synthetic N by the biofertilizer (basal application) did not affect the growth parameters and grain yield of maize; the other treatments usually resulted in lower growth rates and yields, although not statistically significant (p ≥ 0.05). No difference was observed among the treatments for the contents of N, P, K, or Mg in the leaves. Generally, the highest means for Fe, Ca, Cu, Zn, and Mn contents in leaves were observed after in-row broadcast of synthetic fertilizers or basal application of the digestate as a total substitute for synthetic N, with a significant effect for Fe (p < 0.05). The mode of the biofertilizer application did not have any significant effect on either growth parameters or leaf nutrients. The data show that under the specific conditions of the study, the total substitution of mineral N with basal application of biofertilizer is the best strategy for minimizing the use of synthetic chemicals in maize cultivation without yield penalties.
Keywords: anaerobic digestion; bio-based fertilizers; corn growth dynamic; drought stress mitigation; fertilizer application rate/dose; foliar application; methane-rich biogas; nutrient availability; organic fertilizers; soil amendments; waste valorization